2021
DOI: 10.1002/ctm2.276
|View full text |Cite
|
Sign up to set email alerts
|

Iron deficiency promotes aortic medial degeneration via destructing cytoskeleton of vascular smooth muscle cells

Abstract: When iron deficient, the expression of IGTB and Cdc42 in vascular smooth muscle cells (VSMCs) is reduced, while the expression of Rac-1 is increased. In

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Optimal threshold value was obtained from the data, which was the threshold leading to the maximum summation of sensitivity and specificity (i.e., the Youden index). 9 Disease Markers degeneration of the aorta in hypertensive patients [21]. In contrast, Edvinsson et al revealed that compared with normal controls, Cu 2+ and Zn 2+ decreased and Fe 2+ tended to increase in aortic tissue [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optimal threshold value was obtained from the data, which was the threshold leading to the maximum summation of sensitivity and specificity (i.e., the Youden index). 9 Disease Markers degeneration of the aorta in hypertensive patients [21]. In contrast, Edvinsson et al revealed that compared with normal controls, Cu 2+ and Zn 2+ decreased and Fe 2+ tended to increase in aortic tissue [17].…”
Section: Discussionmentioning
confidence: 99%
“…Iron, as one of the essential trace elements for the human body, has received extensive attention for a long time [ 20 ]. Recently, Li et al demonstrated that iron deficiency contributes to the development of medial degeneration of the aorta in hypertensive patients [ 21 ]. In contrast, Edvinsson et al revealed that compared with normal controls, Cu 2+ and Zn 2+ decreased and Fe 2+ tended to increase in aortic tissue [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…37,38 Our previous study demonstrated that ID exacerbated aortic expansion by destroying the cytoskeleton. 8 It is known that the phenotypic switch of VSMCs from stable contractile cells to secretory and proliferative cells is the main underlying mechanism of AMD. 39 In our study, the overexpression of factors related to mitochondrial fission induced phenotypic transformation.…”
Section: Food and Function Papermentioning
confidence: 99%
“…6,7 Our previous study showed that an iron-deficient diet (IDD) degraded the cytoskeleton of the aortic media in mice, which played an important role in the development of AMD. 8…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation